Pendampingan Pembuatan Lilin Aromatik Menggunakan Minyak Jelantah Produksi Rumah Tangga Bagi Ibu-Ibu PKK di Kelurahan Togafo Kecamatan Kota Ternate Barat - Dharmawaty M. Taher; Abdu Mas'ud; Sundari Sundari; Ilham Majid; Syamsul Bahri (BADAN PENERBIT STIEPARI PRESS, 2024)
Creative household waste management can provide environmental and economic benefits for the community. Used cooking oil, which is often considered waste, has the potential to be processed into high-value products such as aromatic candles. These candles are not only useful as an alternative lighting source but also function as fly repellent and aromatherapy that increases the comfort of the home environment. This community service program aims to improve skills and empower PKK mothers in Togafo Village, West Ternate City District, by helping them make aromatic candles from used cooking oil and clove flower stalks. The methods used include initial socialization regarding the benefits and techniques of making aromatic candles, practical training with direct demonstrations, and post-training assistance through routine monitoring and technical assistance. The results of the program show an increase in participants' skills in producing aromatic candles independently, reducing used cooking oil waste, and the potential for developing micro-businesses. This activity has succeeded in empowering the community to manage waste creatively, providing solutions to fly problems, and opening up new economic opportunities, thus becoming a service model that can be replicated in other areas.